Faith in empire : religion, politics, and colonial rule in French Senegal, 1880-1940 - Foster, Elizabeth Ann, 1976- (Stanford University Press, 2013)
'Faith in Empire' is an innovative exploration of French colonial rule in West Africa, conducted through the prism of religion and religious policy. It examines the relationships among French Catholic missionaries, colonial administrators, and Muslim, animist, and Christian Africans in colonial Senegal between 1880 and 1940. In doing so, it illuminates the nature of the relationship between the French Third Republic and its colonies, reveals competing French visions of how to approach Africans, and demonstrates how disparate groups of French and African actors, many of whom were unconnected with the colonial state, shaped French colonial rule.